Effect of Cold Therapy on Pain, Trismus, and Swelling After Third Molar Surgery - Acikan, Izzet; Dündar, Serkan (My University, 2023)
Objective: This study was conducted to evaluate the effectiveness of local cold therapy in reducing pain, swelling, and trismus after third molar surgery. Materials and Methods: Patients who required surgical removal of third molars and met the study criteria were randomly divided into two groups: The cold therapy and the control groups. Patients in the cold therapy group were ordered to use ice packs on the surgical site intermittently after the extraction of the impacted third molar. This first application was followed by the surgeon and was repeated for postoperative day 1. Patients in the control group did not apply cold therapy. Pain, swelling, and trismus were evaluated pre- and postoperatively, and the results were compared between groups. Pain was measured at the 4th, 8th, and 12th hours and on the 1st, 2nd, 5th, and 7th days. The amount of swelling and trismus on postoperative days 2 and 7 and the patients who did not receive cold therapy versus those who received cryotherapy were evaluated. Results: The intensity of pain, swelling, and trismus did not differ significantly between the two groups (p>0.05), except on day 2, when the cold therapy group had a lower pain score than the control group (p<0.05). Conclussion: Thus, it was concluded that cold therapy had no beneficial effect on postoperative complications of impacted third molar surgery.
Keywords: Pain; swelling; third molar; trismus; Cold theraphy